Crowdworking: neue Herausforderungen für das Arbeitsrecht in Deutschland - Dilenge, Michele (IUBH Internationale Hochschule, 2020)
Crowdworking is a new organizational form of work that is attractive for both employees and companies. A great advantage is the flexibility of the design and the need-based access to certain services. Work processes can be made more efficient and flexible. Crowdworking has not yet become an integral part of the labor market. The volume of work performed by crowdworking cannot yet be adequately determined. However, it can be assumed that the Covid 19 pandemic threatens an economic slump that will lead to a reorganization of the work organization. Many employees already
10419/224136
Keywords: Graue Literatur; Arbeitszeit; Arbeitslohn; Crowdworking; Plattformökonomie; Scheinselbständigkeit